The Role of Perceived Control as Mediator in Relationship between Parental Overprotection and Anxiety in Adolscent - Tirza Febe Dama Nanie; Endang Widyorini (Psikostudia : Jurnal Psikologi, 2023)
Anxiety is a condition that often occurs in children, adolescents, and adults. The impacts arising from anxiety, both non-clinical and clinical, are enormous and varied for life. There are many factors that influence developmental anxiety. This study aims to look at the role of perceived control as a mediator in the relationship between parental overprotection and anxiety in adolescents. The population in this study were adolescents aged 12-17 years, attending school in the city of Semarang, and living with their parents with a sample of 55 people participating. The research method used is a correlational quantitative method with the use of scale as a data collection method. There are three scales used in this study, namely the short-form overprotection sub-scale of the Egna Minnen Beträffande Uppfostran (s–EMBU), the Anxiety Control Questionnaire-Children Short Form (ACQ-C), and the anxiety sub-scale. Short version of the Revised Scale. Childhood Anxiety and Depression (RCADS). Data analysis using Regression Analysis Mediator F Hayes. The results obtained in this study are that there is a significant indirect relationship between parental overprotection and anxiety through perceived control (Bootstrap confidence interval range 0.779 to 1.546, not including a zero value) which means that perceived control is a mediator of the parental overprotection relationship to anxiety.Kecemasan merupakan kondisi yang banyak terjadi baik pada anak, remaja, maupun dewasa. Dampak yang timbul akibat kecemasan baik non klinis maupun klinis sangat besar dan bervariasi bagi kehidupan. Ada banyak faktor yang berpengaruh terhadap perkembangan kecemasan. Penelitian ini bertujuan untuk melihat peran dari perceived control sebagai mediator dalam hubungan antara parental overprotection dan kecemasan pada remaja. Populasi dalam penelitian ini adalah remaja berusia 12-17 tahun, bersekolah di Kota Semarang, dan tinggal dengan orang tua dengan sampel yang berpartisipasi sebanyak 55 orang. Metode penelitian yang digunakan adalah metode kuantitatif korelasional dengan penggunaan skala sebagai metode pengambilan data. Ada tiga skala yang digunakan dalam penelitian ini, yaitu sub skala overprotection short-form of the Egna Minnen Beträffande Uppfostran (s–EMBU), Anxiety Control Questionnaire-Children Short Form (ACQ-C), dan sub skala kecemasan Shortened version of the Revised Child Anxiety and Depression Scale (RCADS). Analisis data dengan menggunakan Analisis Regresi Mediator F Hayes. Hasil yang diperoleh dalam penelitian ini adalah adanya hubungan tidak langsung yang signifikan antara parental overprotection dan kecemasan melalui perceived control (Bootstrap rentang interval kepercayaan 0,779 sampai 1,546, tidak mencakup nilai nol) yang artinya perceived control menjadi mediator dari hubungan parental overprotection terhadap kecemasan.